Determination of an efficiency parameter for the use of electric vehicles - Ervand H. Keyan; Alexey N. Melnikov; Olga A. Tamoshina (Вестник СибАДИ, 2025)
Introduction. The main purpose of the work is to determine a parameter characterizing conditions for effective operation of electrically powered vehicles. It has been found that the use of electric vehicles is associated not only with environmental performance, reducing operation costs, but also with limited mobility of both individual owners of passenger cars and owners of commercial vehicles. The limitations are related to the cost of new cars and technical characteristics – power reserve, charging time of traction batteries and charging infrastructure. At the same time, it is necessary to take into account the operating conditions that affect the power reserve, and therefore the number and time of charging operations, which affect the operating cycle length and the maintenance cycle of electric vehicles. The paper presents a mathematical model for efficient operation of electric vehicles, taking into account the relationship of the technical characteristics of cars, charging infrastructure with the purpose and operating conditions of cars.Materials and methods. The results of a survey into opinions of car owners about the conditions of electric vehicles operation, modeling of electric vehicles operation, and classifications have been used. The results and recommendations for the technical operation of electric vehicles are described, depending on the purpose and operating parameters.Results. As intermediate results of the conducted research, the boundary values of the parameter of the efficiency of using electric vehicles were obtained, which makes it possible to justify their operating modes.Discussion. It is noted that the approach implemented in determining the efficiency parameter for electric vehicle operation makes it possible to reasonably carry out measures to develop both the fleet of electric vehicles and the infrastructure that ensures their efficient operation.Conclusion. It has been concluded that the efficiency parameter proposed will make it possible to assess the prospects for the use of electric vehicles, depending on the field of activity and operating conditions.